2022
DOI: 10.1186/s12913-022-07508-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of external social capital in social organizations providing integrated eldercare services with medical care in China

Abstract: Background This study aimed to explore the external social capital of social organizations (SOs) providing integrated eldercare services with medical care in Anhui Province, China. Specifically, we studied the current situation and influencing factors of external social capital and its six dimensions. Methods We conducted a cross-sectional study in Anhui Province, China using a multi-stage stratified random sampling method. We employed Pearson corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…At the same time, due to the relatively small number of services provided, employees can focus on improving service quality and comply with organizational requirements. It has be identified that A previous survey we conducted in Anhui Province showed that the number of services provided by ESOs is also one of the determinants of the choice of nursing home for older adults [ 32 ]. This highlights the need for parity with respect to the number of services offered and the internal social capital of ESOs.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, due to the relatively small number of services provided, employees can focus on improving service quality and comply with organizational requirements. It has be identified that A previous survey we conducted in Anhui Province showed that the number of services provided by ESOs is also one of the determinants of the choice of nursing home for older adults [ 32 ]. This highlights the need for parity with respect to the number of services offered and the internal social capital of ESOs.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional study was conducted in November and December 2019 in Anhui Province, China. Participants were selected through a multi-stage stratified cluster random sampling method [ 9 , 30 ], and a structured questionnaire was used. With the help of local managers, face-to-face interviews were conducted by a skilled and trained survey team from Anhui Medical University.…”
Section: Methodsmentioning
confidence: 99%
“…The theory that underlies this research is a classical theory that states that competitive advantage is influenced by social capital [26,35] and organizational health [23]. Nevertheless, the latest empirical research has also shown that competitive advantage is influenced by social capital [28,31,34,[36][37][38] and organizational health [19][20][21]37] separately. Social capital affects competitive advantage by opening access to a resource that is valuable, rare, inimitable, and non-substitutable [28,35].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The culture and work climate indicators appear to conflict with those proposed to measure the cognitive dimension of social capital. The thing to note is that organizational health emphasizes the internal elements of the organization, in contrast to social capital, which emphasizes external aspects of the organization [36]. In the dimension of accountability, the comprehensive indicator offered can be used, as well as indicators in the coordination and control dimensions that are most likely to be practiced by the same person because of the very flat organizational structure.…”
Section: Organizational Healthmentioning
confidence: 99%